Rekognisi Sistem Pemerintahan Daerah di Indonesia Perspektif Konstitusional - Triwahyuningsih, Triwahyuningsih; Shanty Saleh, Indah Nur (UNES Law Review, 2023)
Philosophically, the State as a forum for realizing national ideals requires a basis that can bring together the various characteristics of Indonesian society. Therefore, a Government of the Republic of Indonesia was formed which was able to protect the entire Indonesian nation and all of Indonesia's blood to prosper the people. The commitment of the Founding Fathers to the special and special rights of regional origin was proven by its inclusion in the Law. The 1945 Constitution of the Republic of Indonesia is hereinafter referred to as the 1945 Constitution. Research objectives: to analyze the importance of recognizing special and special regions within the Unitary State of the Republic of Indonesia based on the 1945 Constitution. Research Method: normative legal research type, data collection method in the form of secondary data with primary legal materials, in the form of statutory regulations and various proclamations. Meanwhile, secondary legal materials are in the form of literature that is relevant to the object under study. This research uses a statutory and historical approach. Qualitative descriptive data analysis method through data display, data reduction and drawing conclusions. The results of the research show: the importance of recognition of special and special regional government systems in Indonesia because recognition is a basic human need in an expanded spectrum, regions within the Unitary State of the Republic of Indonesia want to receive fair treatment from countries that are different from other regions due to historical background factors , culture and position.